Development of stimuli-responsive nano-based pesticides: emerging opportunities for agriculture - Camara, Marcela Candido; Campos, Estefânia Vangelie Ramos; Monteiro, Renata Aparecida; Pereira, Anderson do Espirito Santo; Proença, Patrícia Luiza de Freitas; Fraceto, Leonardo Fernandes (BMC, 2019)
Pesticides and fertilizers are widely used to enhance agriculture yields, although the fraction of the pesticides applied in the field that reaches the targets is less than 0.1%. Such indiscriminate use of chemical pesticides is disadvantageous due to the cost implications and increasing human health and environmental concerns. In recent years, the utilization of nanotechnology to create novel formulations has shown great potential for diminishing the indiscriminate use of pesticides and providing environmentally safer alternatives. Smart nano-based pesticides are designed to efficiently delivery sufficient amounts of active ingredients in response to biotic and/or abiotic stressors that act as triggers, employing targeted and controlled release mechanisms. This review discusses the current status of stimuli-responsive release systems with potential to be used in agriculture, highlighting the challenges and drawbacks that need to be overcome in order to accelerate the global commercialization of smart nanopesticides.
Keywords: Nanopesticides; Triggered release; Smart delivery; Biotic stress; Abiotic stress; Sustainable agriculture